2021
DOI: 10.31764/justek.v4i1.4308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis And Characterization Of Alginate Based Bioplastic With The Addition Of Nanocellulose From Sago Frond As Filler

Abstract: The bioplastic synthesis of alginate in this study has been carried out using nanocellulose from sago fronds as a filler. Bioplastic synthesis uses different nanocellulose concentrations, namely 0%; 0.2%; 0.4%; and 0.6% (w / w). This study aims to see how the characteristics of bioplastics with the addition of nanocellulose. The resulting bioplastics were analyzed for moisture content, solubility, thickness, transmission rate, and transparency. The results of the research on the addition of nanocellulose conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Penelitian mengenai bioplastik diperlukan untuk mendapatkan alternatif plastik yang mudah terurai. Bioplastik adalah plastik yang dapat digunakan seperti plastik konvensional, namun terurai oleh mikroorganisme (bakteri dan jamur), dibuat dari alami disusun oleh bahan organik seperti amilum, kitosan, alginat, agar, lignin, karet, kitin, karagenan, gelatin, polisakarida, protein, pektin, asam lemak dan lilin (Yupa et al, 2021).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian mengenai bioplastik diperlukan untuk mendapatkan alternatif plastik yang mudah terurai. Bioplastik adalah plastik yang dapat digunakan seperti plastik konvensional, namun terurai oleh mikroorganisme (bakteri dan jamur), dibuat dari alami disusun oleh bahan organik seperti amilum, kitosan, alginat, agar, lignin, karet, kitin, karagenan, gelatin, polisakarida, protein, pektin, asam lemak dan lilin (Yupa et al, 2021).…”
Section: Pendahuluanunclassified
“…Uji Ketebalan Bioplastik dilakukan mengacu pada metode Yupa et al (2021), bioplastik diukur menggunakan jangka sorong yang memiliki ketelitian 0,01 mm pada 5 titik yang berbeda. Ketebalan bioplastik diperoleh dari rata-rata hasil pengukuran.…”
Section: Analisis Rendemenunclassified
“…This is because studies have shown that seaweed-based bioplastics have good protective qualities (Lomartire et al, 2022). There are a few types of seaweed-based bioplastics that differ in terms of their source of biomass, like using whole seaweed (Hanry & Surugau, 2020;Moey et al, 2018), agar (Hii et al, 2016), alginate (Castro-Yobal et al, 2021;Yupa et al, 2021), and carrageenan (Farhan & Hani, 2017;Nasution et al, 2019). However, the properties of seaweed-based bioplastics depend on a few factors, starting from the source of biomass until the process of developing bioplastics (Lomartire et al, 2022).…”
Section: 0mentioning
confidence: 99%
“…Next, 1049 cm -1 is C-O streching in aromatic compounds. The C-O functional group of C-O-C with a sharp absorption band and strong intensity is in the fingerprint area with a wavelength of 1049 cm-1 and at a wavelength of 914 which is the C-O fringer print area in alcohol compounds (Bartolucci et al, 2023;Haghighi et al, 2019;Yupa et al, 2021).…”
Section: Ftir Analysismentioning
confidence: 99%